E-Tazkirah Video Streaming Web Portal: a prototype / Sabrina Ahamat - Ahamat, Sabrina (Faculty of Information Technology and Quantitative Sciences, 2006)
Video streaming has become popular technology for delivering any files over the Internet. However, it become more difficult and present many challenge for the developer of this streaming project in order to make it compatible with the new technology. Many analysis had been done in order to ensure the achievement of streaming in the future. This project is focusing on the delivering the live streaming and video on demand (VOD) of the E-Tazkirah Video Streaming Web Portal. This is a prototype project that leads to meet the objectives; to develop a prototype of the E-Tazkirah web portal video streaming, to deliver a live and scheduled video to the user when using the E-Tazkirah web portal video streaming, and to exploit the good way using E-Tazkirah in delivering the video content to user.